A 50 year decennial survey of male Bornean orangutans (Pongo pygmaeus wurmbii) with supplemental genetic analysis in Tanjung Puting National Park, Indonesia - BIRUTÉ MARY GALDIKAS; RUTH ELLA LINSKY; RENIASTOETIE DJOJOASMORO; JOSEPH LORENZ; R. STEVEN WAGNER (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Galdikas BM, Linsky RE, Djojoasmoro R, Lorenz J, Wagner RS. 2023. A 50 year decennial survey of male Bornean orangutans (Pongo pygmaeus wurmbii) with supplemental genetic analysis in Tanjung Puting National Park, Indonesia. Biodiversitas 24: 2587-2595. This study investigates the declining presence of adult males in a protected wild population of Bornean orangutans (Pongo pygmaeus wurmbii) at the Camp Leakey study area in Tanjung Puting National Park (TPNP), Central Kalimantan, Indonesian Borneo. Orangutan populations are in decline due to habitat destruction and fragmentation. Documenting changes within existing orangutan populations over time is important to understand demographic changes that may indicate pre-extinction processes and imminent collapse. Wild orangutan behavior has been studied at Camp Leakey since 1971. Observations of orangutans over the past five decades have documented a greatly decreased number of encounters with flanged adult males. A supplementary six-month genetic study was hindered by the fact that only two adult males briefly appeared in the study area in 2016 as compared to 40 adult male encounters in the same time period in 1976. The decline which appears most visible in data from 1986 to 1996 continues into 2006 and 2016. Genotypes from 24 wild adult orangutans encountered in 2016 were analyzed to assess the expected genetic parameters of a wild orangutan population. Pairwise relatedness was high among and between adult females and subadult males. The only two flanged males present during the genetic survey shared zero pairwise relatednesses. However, both flanged males had non-zero pairwise relatedness with other members of the Camp Leakey community and thus it is likely they were from different local areas. These data show the genetic consequences of the observed demographic changes. As TPNP forests have become disconnected from neighboring habitats, natural orangutan male dispersal may be disrupted. Disruption of male dispersal would increase the risk of accelerated extirpation for the orangutan population in TPNP as well as other orangutan populations, especially those that are remnant and less protected.